KAJIAN GENDER DALAM PENYELENGGARAAN PENDIDIKAN DISEKOLAH DASAR - Ananda, Rizki; Azru Sauqi, Nayya; Aulia, Riska; Mahmuda, Wadda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education in Primary Schools. This research utilizes a qualitative descriptive method with a Systematic Literature Review (SLR) approach by reviewing various journals, scientific articles, and relevant sources related to gender and primary education. Data were collected through the process of identifying, selecting, analyzing, and synthesizing literature that aligns with the research topic. The results indicate that gender issues in primary education remain a crucial concern, particularly regarding equal access to education, the role of teachers in shaping gender perspectives, the use of teaching materials, and interaction patterns within the school environment. Gender-responsive education can create a fair, inclusive, and non-discriminatory learning environment for both male and female students. Furthermore, the implementation of gender equality-based education can optimize students' learning participation, self-confidence, and social development. Therefore, collaboration among schools, teachers, parents, and the government is essential to realize gender-equitable primary education.